EFFECTS OF SIX PERSONALITY FACTORS OF CEOs AT SMALL AND MEDIUM-SIZED ENTERPRISES ON PERFORMANCE IN BUSINESS MANAGEMENT: FOCUSING ON LEARNING AND GROWTH - Man-pil Han; Bong-ihn Seok; Joon-ho Kim (Asian Academy of Management Journal, 2017)
For the continual growth of small and medium-sized enterprises (SMEs) in the era of quickly changing economic paradigms, the role of the chief executive officer (CEO) is more important than ever. Because the role of a CEO is the core factor determining performance in business management, the behavioural characteristics of CEOs can determine the outcomes in a company. This study was conducted from the viewpoint that personality factors contribute to behavioural characteristics. The causal relationships were analysed among the six HEXACO personality factors (honesty-humility, extroversion, conscientiousness, agreeableness, openness to experience, and emotionality), the learning and growth of organisations, and performance in business management. For this purpose, a survey was conducted of the current CEOs of SMEs over a period of approximately 10 months, extending from 21 May 2015 to 22 February 2016. A total of 172 valid data were collected and used for the analysis of this study, and the results were as follows. First, among the six personality factors of CEOs, conscientiousness and openness to experience were shown to have a positive effect on learning and growth, determining the organisation’s work management and innovation. Second, agreeableness was shown to have a positive effect on performance in business management. Third, learning and growth were shown to have positive effects on performance in business management.